Stress concentration analysis of a composite patch on a hole in an isotropic plate - Aabid, Abdul; Hrairi, Meftah; Mohamed Ali, Jaffar Syed; Abuzaid, Ahmed (Trans Stellar, 2018)
In aerospace engineering design, structures with holes have been widely considered. However, these types of structures have the potential to produce critical crack growth since the stress concentration is high. This paper investigates the stress concentration factor (SCF) in a plate with a circular hole that is adhesively bonded with a composite patch placed on hole. The plate material considered is aluminum 2024-T3under uniform tensile load. The effect of the composite material on the circular hole in the plate was analyzed using the finite element method (FEM). From the present simulation results, it has been observed that the SCF is affected by the composite material patches. The stress distribution was estimated as an effectiveness criterion from the SCF. However, these effects are also dependent on the adhesive bond, patch material, patch dimensions, and the hole diameter.